Embedding DSP control algorithms in PSpice - Detjen, D.; Schroder, S.; De Doncker, R.W. (IEEE transactions on power electronics, 2003)
A new method is developed to embed DSP control algorithms into PSpice providing accurate time stamped simulation of real-time applications. The proposed method allows to build new PSpice models with an arbitrary number of external nodes using PSpice's Device Equation option. Sampled systems can be simulated including the effects of discrete sampling times as well as propagation delays caused by processors. Control code developed in C-language can be embedded into this PSpice control model prior to downloading into the real-time DSP environment. To verify the simulation approach, simulation results and experimental results of a shunt active filter for harmonic current compensation in a three-phase system are presented.